Evaluation of TLR-2 sera levels in a sample of Iraqi pulmonary TB patients - Ali, Lara Ghali A.; Utba, Nawal Mohammed; Mankhi, Ahmed Asmer (Iraqi Journal of Science, 2018)
The non-specific response of immunity has developed as the initial barrier for human protection from invading pathogens, which comprises certain pathogen recognition receptors (PRR) for instance toll-like receptors (TLRs). Toll like receptor 2 (TLR 2) is capable of recognizing pathogen associated molecular patterns (PAMP) coded by Mycobacterium tuberculosis. To evaluate TLR 2 level in sera of pulmonary tuberculosis (TB) patients. About 120 subjects, involving 80 patients with pulmonary TB including 40 multiple drug resistance (MDR), 20 recently diagnosed pulmonary TB (RD) and 20 recurrent TB patients named as old cases (OC), in addition to 40 apparently healthy individuals were studied as control group. Sera from 68 TB patients and 20 healthy controls were obtained for measuring TLR 2 levels by enzyme linked immunosorbent assay (ELISA). The present result revealed that serum levels of TLR 2 showed there is no significant differences between each patient's group and control except OC group given that, has decreased significantly (p<0.05). The mean ±SD of TLR 2 level in MDR, RD, OC and controls were 4.0± 2.4, 3.4±1.4, 2.2±0.9 and 4.1± 3.0 ng/ml, respectively. The results exhibited that during treatment of tuberculosis, patients with pulmonary tuberculosis showed elevated TLR 2 concentration, which looks probably in charge of regulating inflammation and infection. Consequently, this study proposes that killing of MTB could occur in the time of disease management because of effective treatment, in addition to activation and releasing of different immune system mediators via TLR 2.